2017
DOI: 10.21608/jssae.2017.37490
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Amino Acids and Humic Substances Application on Some Soil Chemical Properties Along with Nutritional Status and Productivity of Wheat Grown under Saline Conditions

Abstract: A field experiment was carried out on saline sandy clay loam soil at Gelbana Village District Sahl-el Tina, North Sinai Governorate, Egypt during two successive winter seasons (2013/2014 and 2014/2015) to study the effect of amino acids (A) , humic substances (H) and amino humate (AH) on soil chemical properties along with nutritional status and productivity of wheat grown under salinity stress condition, using a complete randomized block design with three replicates. The soil was irrigated from El-Salam Cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…( Salama et al, 2015 , Dawood, 2016 , Roychoudhury and Banerjee, 2016 ). These data are compatible with those of Kenawy and Mona (2017) , who found that adding Humic acid to saline soils decreased the electrical conductivity of the soil (EC).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…( Salama et al, 2015 , Dawood, 2016 , Roychoudhury and Banerjee, 2016 ). These data are compatible with those of Kenawy and Mona (2017) , who found that adding Humic acid to saline soils decreased the electrical conductivity of the soil (EC).…”
Section: Discussionsupporting
confidence: 92%
“…Molasses (Sugar beet extract) is a by-product of the sugar manufacturing from sugar beets; it is a cheap and available material; sugar beet extract contains a considerable amount of GB and a range of other essential nutrients Abdelmotlb et al (2019) . Humic acid is widely used as a soil conditioner and growth regulator Kenawy and Mona (2017) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…K-humate raised the organic matter in the soil by 13% compared to the control. The positive effect of K-humate in increasing the availability of nutrients in the soil is through the formation of organic complexes that preserve them from fixation factors and reduce their leaching chances (Kenawy 2017;Dinçsoy and Sönmez 2019). These outcomes are a result of the organic matter concentration (65-70%) of humic compounds in Khumate.…”
Section: Discussionmentioning
confidence: 99%